Butyrate Alleviates Cytokine-Induced Barrier Dysfunction by Modifying Claudin-2 Levels - Xinyi Huang; Tadayuki Oshima; Toshihiko Tomita; Hirokazu Fukui; Hiroto Miwa (Biology, 2021)
Gastrointestinal (GI) disorders such as celiac disease and inflammatory bowel disease are attributed to intestinal barrier disruption. Imbalance of cytokines has been reported in the intestinal epithelium of patients with GI disorders. Short-chain fatty acids (SCFAs), derived from the fermentation of dietary fiber in the intestine, have been reported to benefit the intestinal barrier. Accordingly, we evaluated the effect of specific SCFAs on intestinal barrier function under cytokine-stimulated conditions. Caco-2 cells were cultured on insert membranes to generate monolayers, which then were used to investigate the effects of SCFAs. Tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), or interleukin-13 (IL-13) was added to the basolateral side of the membrane while SCFAs were added to the apical side. After a 24 h stimulation, transepithelial electrical resistance (TEER) was measured, and the protein levels of claudin-1, claudin-2, claudin-3, claudin-4, occludin, and zonula occludens-1 (ZO-1) were evaluated by Western blot. Butyrate, but not acetate, propionate, or succinate, ameliorated the TNF-α/IFN-γ-induced decrease in TEER. TNF-α/IFN-γ stimulation significantly increased the protein level of claudin-2 and decreased the level of claudin-3. Butyrate significantly attenuated the upregulation of claudin-2 induced by TNF-α/IFN-γ. Butyrate blocked the decrease in TEER and the upregulation of claudin-2 induced by IL-13 without changing the level of other tight junction proteins. Our results suggested that butyrate is the main component of SCFAs to alleviate barrier dysfunction and that claudin-2 is the major target of this SCFA.